Tissue Distribution of Parrot Bornavirus 4 (PaBV-4) in Experimentally Infected Young and Adult Cockatiels (Nymphicus hollandicus) - Jana Petzold; Anna Maria Gartner; Sara Malberg; Jessica Bianca Link; Bianca Bücking; Michael Lierz; Christiane Herden (Viruses, 2022)
Proventricular dilatation disease (PDD) caused by parrot bornavirus (PaBV) infection is an often-fatal disease known to infect Psittaciformes. The impact of age at the time of PaBV infection on organ lesions and tissue distribution of virus antigen and RNA remains largely unclear. For this purpose, tissue sections of 11 cockatiels intravenously infected with PaBV-4 as adults or juveniles, respectively, were examined via histology, immunohistochemistry applying a phosphoprotein (P) antibody directed against the bornaviral phosphoprotein and in situ hybridisation to detect viral RNA in tissues. In both groups of adult- and juvenile-infected cockatiels, widespread tissue distribution of bornaviral antigen and RNA as well as histologic inflammatory lesions were demonstrated. The latter appeared more severe in the central nervous system in adults and in the proventriculus of juveniles, respectively. During the study, central nervous symptoms and signs of gastrointestinal affection were only demonstrated in adult birds. Our findings indicate a great role of the age at the time of infection in the development of histopathological lesions and clinical signs, and thus provide a better understanding of the pathogenesis, possible virus transmission routes, and the development of carrier birds posing a risk to psittacine collections.